FACTORS SUPPORTING TEACHING AND LEARNING ENGLISH IN NON-ENGLISH SPEAKING COUNTRIES (ResearchJet Journal of Analysis and Inventions, 2021)
This paragraph of the graduation paper is devoted to the issues of the factors supporting teaching in non-English speaking countries. The participation of learners in the design of an ESP course is essential in order for the course to be effective. Teachers may rely more often on intuition when making course planning than on informed assessment of learners needs.